Social participation in designing urban spaces related to green areas on the example of Białystok - Rawski, Kamil (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
Social participation is a tool thanks to which newly designed places can be adapted to the needs of residents as much as possible. People can also decide to extend the functional program of the housing estates where they live. Therefore, this phenomenon has a real influence on shaping their close surroundings. The article analyses how social participation takes place in Bialystok on the example of the Civic Budget organized by the Municipal Office.